Human Development through the Lens of Digital Literacy - Debbra Toria Nipo; Jaratin Lily; Sidah Idris; Saizal Pinjaman; Imbarine Bujang (2020)
Digital inclusion has now become not only a matter of technological adoption, but the ability to use technologies where individuals are to possess necessary skills to make effective use of digital technologies. In this regard, digital literacy is seen as a crucial enabler for individuals to take advantage of digital opportunities as well as to engage in digital activities. Building on the importance of digital literacy, this study therefore attempts to assess the role of Internet usage and digital literacy on human development, which is proxied by the Human Development Index (HDI). Using a panel dataset covering 38 countries over a 4-year time span from 2015 to 2018, results of regression analysis indicate that both Internet usage and digital literacy emerge with significant and positive relationships with HDI. This evidence suggests that the high number of Internet users and high level of digital literacy are important means for promoting human development. Additional moderation analysis between Internet usage and digital literacy also produces a positive and significant interaction effect, which subsequently implies that digital literacy is an essential skill in enhancing effective usage of the Internet towards achieving greater socioeconomic well-being.